The complete plastid genome of Magnolia omeiensis (Magnoliaceae) - Nan Zhao; Lu Liu; Yu-Qu Zhang; Hai-Fei Yan; Tong-Jian Liu; Hui-Run Huang (Mitochondrial DNA. Part B. Resources, 2019)
Magnolia omeiensis (W. C. Cheng) Dandy, belonging to Magnolia sect. Gynopodium Dandy (Magnoliaceae), is a critically endangered species. In this study, we assembled the complete plastid genome sequence of M. omeiensis. The plastid genome was 160,091 bp in length, consisting of a large single-copy (LSC) region of 88,160 bp, a small single-copy (SSC) region of 18,763 bp, and two inverted repeat (IR) regions of 26,584 bp. It contained 112 unique genes, including 80 protein-coding genes, 28 tRNA genes, and 4 rRNA genes. Overall GC content was 39.3%. Phylogenetic analysis showed that M. omeiensis was closely related to Magnolia Yunnanensis, which was identified in the same section Gynopodium.